Legal regulation of the inheritance of personal electronic assets - Адаховська, Надія Сергіївна; Адаховська, Н. С.; Адаховская, Надежда Сергеевна; Adakhovska, Nadiia S.; Омельчук, Олександр Сергійович; Омельчук, О. С.; Омельчук, Александр Сергеевич; Omelchuk, Oleksandr S.; Гофман, Олександр Рудольфович; Гофман, О. Р.; Гофман, Александр Рудольфович; Hofman, Oleksandr R.; et al. (Universidad de la Amazonia, 2019)
The article is devoted to issues of inheritance of such digital assets as personal pages and accounts. The peculiarities of the legal nature of these objects of legal protection are determined, the interdependence between the peculiarities of the legal nature of electronic assets and the legal regime of their inheritance is determined. The article analyzes the norms of the current legislation and defines the problematic moments of the application of the norms governing the similar relations in relation to the investigated relations. The factors influencing the legal mode of information from online correspondence are determined.

Статтю присвячено питанням спадкування таких цифрових активів як персональні сторінки та облікові записи. З’ясовано особливості правової природи даних об’єктів правового захисту, визначено взаємозалежності між особливостями правової природи електронних активів та правовим режимом їх спадкування. Проаналізовано норми чинного законодавства та визначено проблемні моменти з астосування норм, що регулюють схожі за змістом відносини до досліджуваних відносин. Визначено фактори, що чинять вплив на правовий режим інформації з онлайн-кореспонденції.
Adakhovska N. Legal regulation of the inheritance of personal electronic assets / N. Adakhovska, O. Omelchuk, O. Gofman, H. Budurova, S. Alina // Amazonia Investiga. - Vol. 8. - Issue: 21. - Universidad de la Amazonia, 2019. - Р. 321-325.
Keywords: inheritance of electronic assets virtual property, the mystery of correspondence, the right to privacy; virtual property; mystery of correspondence; right to privacy; спадкування електронних активів; віртуальне майно; таємниця листування; право на приватність; Research Subject Categories::LAW/JURISPRUDENCE